TOURISM PROMOTION STRATEGY OF THE DINAS KEPEMUDAAN OLAHRAGA DAN PARIWISATA OF PONTIANAK CITY IN INCREASING TOURIST VISITS - Supiati; Bob Andrian; Evi Hafizah (Universitas Islam Negeri Mataram, 2022)
This research focuses on the development strategy of tourist visits to Pontianak City from 2016 to 2020. The research is aimed at finding out how the promotion strategy of the Tourism Sector increases tourist visits at the Pontianak City DISPORAPAR in 2019. This research uses descriptive qualitative methods with observation, interview, and documentation techniques. The results of the study that the Tourism Promotion Strategy in increasing tourist visits went through three stages. Planning is carried out through setting a promotional budget, determining the target market analysis, promotion goals, and message planning. Tahap implementation activities by carrying out promotional activities, using promotional media, and tourism events. While the evaluation stage is an evaluation meeting, a report on the performance of responsibility for one period.